Elevated mycophenolic acid levels after kidney transplantation: avoiding unnecessary dose reduction through team-based TDM interpretation - Śmiertka, Angelika; Cios, Agnieszka; Hońdo, Łukasz; Supernak , Agnieszka; Grzywa, Anna; Sobczyńska , Katarzyna; Krzanowska, Katarzyna; Wesołowska, Anna (Folia Medica Cracoviensia, 2026)
Mycophenolate mofetil (MMF) is a cornerstone immunosuppressive agent used in combination with calcineurin inhibitors and corticosteroids to prevent acute allograft rejection in solid organ transplant recipients. Long-term transplant outcomes depend not only on the pharmacological efficacy of immunosuppressive regimens but also on individualized dosing strategies and sustained medication adherence. Owing to the complex and highly variable pharmacokinetics of MMF’s active metabolite, mycophenolic acid (MPA), therapeutic drug monitoring (TDM) has become an important tool for optimizing treatment safety and efficacy. We report a case of a kidney transplant recipient with unexpectedly elevated MPA exposure in the absence of clinical toxicity. A detailed pharmacokinetic assessment combined with a comprehensive clinical pharmacist- led medication review indicated that the increased MPA concentrations and elevated AUC0-12h were most likely related to impaired renal elimination of mycophenolic acid glucuronide (MPAG). Reduced MPAG clearance may enhance enterohepatic recirculation (EHR) of MPA, resulting in increased systemic exposure. This case highlights the importance of interpreting elevated MPA concentrations within a broader clinical context and underscores the critical role of clinical pharmacists, as members of an interdisciplinary team, in integrating TDM with comprehensive pharmacokinetic assessment to ensure safe and effective long-term immunosuppressive therapy.